2018
DOI: 10.20517/2394-4722.2018.06
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer cells at a therapeutic gunpoint of the autophagy process

Abstract: In a normal prostate, the process of controling cell death is essential to maintain tissue homeostasis and its inhibition may lead to the development of cancer. Androgen receptor signaling plays pivotal roles in the prostate development and homeostasis as well as in the progression of prostate cancer. The main treatment for prostate cancer is a combination of androgen deprivation therapy (ADT) using anti-androgens and docetaxil administration. However, ADT eventually fails due to a pathological unbalance of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 100 publications
(133 reference statements)
0
7
0
Order By: Relevance
“…In the cellular environment, PKM2 is associated with protein kinase B (Akt)/mechanistic or mammalian target of rapamycin (mTOR) signaling pathway [33], which regulates numerous cellular processes, including cell growth and survival, cell cycle progression, protein synthesis, and angiogenesis [34]. Activation of the Akt/mTOR pathway impairs autophagy in prostate cancer cells [34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the cellular environment, PKM2 is associated with protein kinase B (Akt)/mechanistic or mammalian target of rapamycin (mTOR) signaling pathway [33], which regulates numerous cellular processes, including cell growth and survival, cell cycle progression, protein synthesis, and angiogenesis [34]. Activation of the Akt/mTOR pathway impairs autophagy in prostate cancer cells [34].…”
Section: Introductionmentioning
confidence: 99%
“…In the cellular environment, PKM2 is associated with protein kinase B (Akt)/mechanistic or mammalian target of rapamycin (mTOR) signaling pathway [33], which regulates numerous cellular processes, including cell growth and survival, cell cycle progression, protein synthesis, and angiogenesis [34]. Activation of the Akt/mTOR pathway impairs autophagy in prostate cancer cells [34]. Autophagy is a well-regulated homeostatic mechanism characterized by the collection of the cytoplasmic machinery into autophagosomes, followed by its lysosomal proteolytic digestion and recycling to maintain cellular growth [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, testosterone, a hormone produced in the testicles, may further stimulate prostate hyperplasia in some patients [3]. Most advanced prostate cancer patients evolve an uncontrollable castration-resistant prostate cancer (CRPC), resulting in scantiness of hormones in the body and increasing the difficulty for prostate cancer treatments [4]. Therefore, it is more and more important to research a new and curative treatment program for prostate cancer through modulating immune balance with low cytotoxic and effective compounds from different food and herb materi-the number of T lymphocytes (CD4 + and CD8 + ) in BALB/c CT 26 tumor-bearing mice [25].…”
Section: Introductionmentioning
confidence: 99%
“…Light chain 3 (LC3), is essential for autophagy and serves as a vital component in monitoring autophagy and visualizing autophagosomes in vivo [15]. Pyruvate kinase M2 isoform (PKM2), a rate-limiting terminal glycolytic enzyme, catalyzes the last step of glycolysis, and recent studies have reported that PKM2 is associated with the Akt signal pathway, which regulates cell survival and apoptosis [16,17]. Meanwhile, many cellular signals have been reported to be involved in the regulation of autophagy, including the Akt (protein kinase B)-mTOR (mammalian target of rapamycin) pathway [18,19].…”
mentioning
confidence: 99%